Design and preparation of core–shell AP@HNS composites with high safety and excellent thermal decomposition performance. Issue 24 (19th May 2022) - Li, Wenxiang; Ye, Ping; Guo, Changping; Zhu, Wenkun; Jin, Dayong
Abstract : AP@HNS composites with core–shell structure were designed and prepared. This technology is expected to provide new ideas for designing and preparing solid propellants with high energy, low susceptibility, and excellent thermal decomposition performance. Abstract : Solid propellants with high safety, excellent thermal decomposition, and green performance are hot and difficult research areas in aerospace. In this paper, AP@HNS (hexanitrostilbene) composites with core–shell structure were designed and prepared by an ultrasound-assisted method using polyurethane for the interfacial modification of ammonium perchlorate (AP). The results show that the AP@HNS composites have a complete and dense shell structure when the nano-HNS content of the shell layer is 15% or more, the synergistic decomposition effect between HNS and AP can advance the high-temperature decomposition peak of AP by 102.4 °C and increase the apparent heat release 2.55 times to 1388 J g −1, and HNS improves the energy of AP while reducing environmental pollution. The safety performance test shows that the nano-HNS with 15% mass content can increase the composite characteristic drop height H 50 to 32 cm and reduce the frictional susceptibility explosion probability to 77% (the H 50 of AP is 27 cm and the frictional susceptibility explosion probability is 95%). The insensitive shell layer HNS significantly improves the safety performance of AP through barrier and buffering effects. This technology is expected to provide new ideas for designing and preparing solid propellants with high energy, low susceptibility, and excellent thermal decomposition performance.